Web-enabled smart home using wireless node infrastructure - Mantoro, Teddy; Ayu, Media Anugerah; Elnour, Elbara (2011)
This paper presents a framework for a smart home which uses wireless nodes infrastructure. The framework is developed based on the aims to build a smart home that can be implemented easily without the hassle of major alteration to current condition of the house. A prototype which built based on the proposed framework is presented as a proof of concept of its implementation. The prototype, which we called Integ’s Smart Home system, allows its occupant to control the home through the Internet, Wi-Fi and GPRS enabled mobile devices. Simulation results on a typical home occupant’s whole day activities during working days and non working days are presented and discussed. The result shows that the occupant spent their time mostly at home, not outside, either during working day (65%) or non working day (93.75%). This results show that home is a very important place for its occupant.